Techniques for laparoscopic liver parenchymal transection - Yoh, Tomoaki (Hepatobiliary Surg Nutr, 2019)
Laparoscopic liver surgery has gained wide acceptance resulting in a paradigm shift of liver surgery. Technical innovations and accumulation of surgeon’s experience have allowed laparoscopic liver resection (LLR) to become an effective procedure with favorable peri- and post-operative outcomes. Through the overall process of LLR, liver parenchymal transection remains the most critical step with the aim of minimizing blood loss and secures the appropriate cutting line, i.e., securing major vessels and obtaining adequate surgical margin clearance for malignancies. Multiple preoperative imaging modalities and intraoperative ultrasonography findings may contribute to the best determination of the appropriate cutting line during the LLR; however, technical expertise in minimizing and controlling bleeding during liver parenchymal transection is still a challenge for safe LLR, and therefore represents a major concern for hepatobiliary surgeons. Along with the historical fact that the technique of liver parenchymal transection itself is chosen according to surgeon’s preference and “savoir-faire”, the best technical modality in laparoscopic liver parenchymal transection remains to be determined. However, better understanding the technical issue may serve a contribution to the standardization of LLR. This review article therefore focuses on the technical aspects of the laparoscopic liver parenchymal transection.